Toward sustainable development: the nexus between financial development, renewable energy, and carbon emissions in China - Sun, Yang; Zhao, Feng; Gao, Liya (Frontiers in Environmental Science, 2025)
The accelerating emissions of greenhouse gases—particularly carbon dioxide (CO2)—pose serious challenges to global environmental sustainability, with China being a major contributor due to its rapid economic and financial expansion. This study investigates the nexus between financial development (FD), renewable energy consumption, and CO2 emissions in China over the period 1996–2022. Using advanced time-series econometric methods, including dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS), canonical cointegration regression (CCR), and Granger causality analysis, this study aims to uncover the long-run relationships and causal directions among economic growth, financial development, renewable energy use, human capital, agricultural productivity, and carbon emissions (CEs). The findings reveal five key results: (1) economic growth is positively associated with CO2 emissions, confirming an environmental trade-off; (2) financial development also significantly increases emissions, indicating potential ecological risks from financial sector expansion; (3) renewable energy consumption significantly reduces CO2 emissions, confirming its role in promoting environmental quality; (4) human capital and agricultural productivity both contribute to emission reduction; and (5) causality tests show unidirectional and bidirectional relationships among variables, highlighting the interdependence of energy, finance, and environmental dynamics. The study concludes that China can reduce carbon emissions without compromising economic growth by accelerating renewable energy adoption, investing in green technologies, and promoting sustainable agricultural practices through targeted environmental and economic policies.